Adsorptive polyHIPE composites based on biosorbent immobilized nanoclay: Effects of immobilization techniques. Issue 8 (1st August 2017) - Mert, Hatice Hande; Tekay, Emre; Nugay, Nihan; Nugay, Turgut; Şen, Sinan
Abstract : Styrene/divinyl benzene‐based macroporous polyHIPE composites were prepared from water‐in‐oil (w/o) high internal phase emulsion (HIPE) templates by using both organo‐modified montmorillonite (MMT) and a nonionic surfactant. For this purpose, Spirulina (Sp) microalgae was immobilized onto Na‐MMT clay by using two different modification techniques. They are based on conventional adsorption in solution (SOL) and novel cryoscopic expansion (C‐XP) assisted adsorption. Highly porous nanocomposites were prepared by using different percentages of modified nanoclays (SpSOLM/SpXPM) with a constant internal phase volume of 80%. The emulsion stability, morphology, and dye adsorption capacities were discussed by paying attention to nanoclay immobilization techniques, clay loading degree and surfactant concentration. The critical amount of nonionic surfactant for formation of the stable neat HIPE template was found to be only 5 vol% with respect to volume of organic phase. However, this amount was further reduced to much less value (2 vol%) with Sp immobilized nanoclays via help of cooperative interactions of Sp and MMT nanoclay. The C‐XP assisted modification of clay led to nanocomposites with 580% higher adsorption capacity for cationic dye. This remarkable benefit was obtained with even 0.5% clay loading and only 2% surfactant concentration. POLYM. ENG. SCI., 58:1229–1240, 2018. © 2017 Society of Plastics Engineers